Preparation and Characterisation of Cellulose Acetate and Carboxymethyl Cellulose from Edible Part and Peel of Green Banana (Plantain) - Monira, Sumyea; Akter, Momota; Rahman, SM Mizanur; Rahman, M Azizur (Dhaka University Journal of Science, 2017)
Abstract not available Dhaka Univ. J. Sci. 65(1): 81-82, 2017 (January)